PERANCANGAN DAN IMPLEMENTASI PERANGKAT LUNAK SISTEM PENCOCOKAN SIDIK JARI DENGAN ALGORITMA FILTERBANK GABOR - Widodo, Aris Puji; Adi, Kusworo (MATEMATIKA, 2006)
From research result used filterbank gabor algorithms, can give 96 (24 x 4) featurres from 24 sector with 4 filter. Gabor filter use 23 x 23 with orientation change 00, 450, 900, dan 1350. Each orientation angle change will be rotation gabor filter on to its. Make feature vector or FingerCode with Avarage Absolute Deviation (AAD) are average value from difference pixels number for each sector and centre value on sector. Error system on disjoint between FAR dan FRR with value 3,6% and threshold value 39. Then slope from GAR graphic value 400, this is proving that this system is running a good, cause slope recommendation value 450.